Integrating the One Map Policy into the One Data Policy within the Pontianak City Government - Kurniawan, Muhammad (Uniplan: Journal of Urban and Regional Planning, 2023)
In the pursuit of implementing the one-map policy through the establishment of a Regional Geospatial Information Network (JIGD), the Pontianak City Government is potentially confronted with issues of inefficiency. JIGD possibly resembled the existing data management system, namely the One Data Indonesia system (SDI) that is well established since 2019. This study analyzed the possibility of whether to build JIGD as a standalone structure or to integrate it into SDI to address inefficiency issue. Employing a qualitative methodology, this study embarked on a comprehensive literature review encompassing both general data types and spatial information within the data management system to understand the nature of the data and the surrounding environment. Those then were analyzed based on the data characteristics, the organizational structure, supporting technology, human resources, and applicable regulations regarding it. The results suggested that integration is more feasible but should modify the organizational structure of the existing SDI system.